Evaluation of the Jönköping dental fear coping model: a patient perspective. (3rd April 2019) - Brahm, Carl-Otto; Lundgren, Jesper; Carlsson, Sven G.; Nilsson, Peter; Hägglin, Catharina
Abstract: Objective: This study is a part of a project with the aim to construct and evaluate a structured treatment model (the Jönköping Dental Fear Coping Model, DFCM) for the treatment of dental patients. The aim of the present study was to evaluate the DFCM from a patient perspective. Material and methods: The study was performed at four Public Dental Clinics, with the same 13 dentists and 14 dental hygienists participating in two treatment periods. In Period I, 1351 patients were included and in Period II, 1417. Standard care was used in Period I, and in Period II the professionals had been trained in and worked according to the DFCM. In the evaluation, the outcome measures were self-rated discomfort, pain and tension, and satisfaction with the professionals. Results: In comparison with standard care, less tension was reported among patients treated according to the DFCM, ( p = .041), which was also found among female patients in a subgroup analysis ( p = .028). Additional subgroup analyses revealed that patients expecting dental treatment (as opposed to examination only) reported less discomfort ( p = .033), pain ( p = .016) and tension ( p = .012) in Period II than in Period I. Patients with low to moderate dental fear reported less pain in Period II than in Period I ( p = .014). Conclusions: The DFCM has several positive effects on adult patients in routine dental care. In a Swedish context, the differences between standard care and treatment according to the model were small but, in part, statistically significant. However, it is important to evaluate the model in further studies to allow generalization to other settings.